Enhanced Gold nanoparticle Optics for Nanophotonics, Photovoltaics and Green Photonics insights - Bracamonte, Angel Guillermo (2023)
In this communication it was developed the basis of Nanotechnology and fundamental Research focused on Nanophotonics and Green Photonics for Biophotonics and Implantable devices with varied interest and applications. Thus, gold Nanoparticles as Optical active Nanomaterials presented different advantages in comparison to other materials due to their biocompatibility, low toxicity depending of chemistry of surfaces, and capability to generate high Electromagnetic fields known as Plasmonics properties. In addition gold Nano-surfaces are relatively easy to be conjugated with other materials due to their soft electronic bonding and polarizable surfaces. These characteristics provide to gold Nanoparticles interesting insights and future perspectives within Nanophotonics and Green Photonics developments. Thus, Nanophotonics based on gold Nanomaterials provide excellent light matter interactions accompanied with the generation of varied quantum and non-classical light properties. In this context, it should be noted recent trends of Green Photonics where materials and associated properties should be biocompatible contemplating their fabrication too. It is a great challenge to develop Green Nanomaterials with Enhanced conductive and luminescent properties; however gold based Nanomaterials are showing interesting insights within Nanotechnology. In these perspectives and looking for new Optical active materials it should be highlighted the design and fabrication of devices from the Nanoscale and beyond. And, it should be highlighted the particular interest on Implantable Optical active devices due to their potential perspectives within Life Sciences. Therefore, in this short Review it was intended to afford to discuss about how gold Nanomaterials could provide insights within Nanophotonics, Green Photonics, and Life Science applications.